Mechanistic investigation of a visible light mediated dehalogenation/cyclisation reaction using iron(iii), iridium(iii) and ruthenium(ii) photosensitizers. Issue 24 (15th November 2021) - Aydogan, Akin; Bangle, Rachel E.; De Kreijger, Simon; Dickenson, John C.; Singleton, Michael L.; Cauët, Emilie; Cadranel, Alejandro; Meyer, Gerald J.; Elias, Benjamin; Sampaio, Renato N.; Troian-Gautier, Ludovic
Abstract : The identification of reaction mechanisms unique to the iron, ruthenium, and iridium PS represents progress towards the long-sought goal of utilizing earth-abundant, first-row transition metals for emerging energy and environmental applications. Abstract : The mechanism of a visible light-driven dehalogenation/cyclization reaction was investigated using ruthenium(ii ), iridium(iii ) and iron(iii ) photosensitizers by means of steady-state photoluminescence, time-resolved infrared spectroscopy, and nanosecond/femtosecond transient absorption spectroscopy. The nature of the photosensitizer was found to influence the product distribution such that the dehalogenated, non-cyclized products were only detected for the iron photosensitizer. Strikingly, with the iron photosensitizer, large catalytic yields required a low dielectric solvent such as dichloromethane, consistent with a previous publication. This low dielectric solvent allowed ultrafast charge-separation to outcompete geminate charge recombination and improved cage escape efficiency. Further, the identification of reaction mechanisms unique to the iron, ruthenium, and iridium photosensitizer represents progress towards the long-sought goal of utilizing earth-abundant, first-row transition metals for emerging energy and environmental applications.